Pengembangan Media Pembelajaran Digital T’Smart Berbasis Teka-Teki Silang Berbantuan Canva Materi Pencernaan Manusia Kelas V SDN 2 Tiudan Kabupaten Tulungagung - Febriani, Icha; Jadmiko, Rahmad Setyo; Oktaviarini, Nourma (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Science learning on the human digestive system still faces limitations in the use of interactive digital media, so learning tends to be one-way. This condition indicates the need for media that combines material presentation with educational games. This study aims to develop a digital learning media T'Smart based on crossword puzzles assisted by Canva on the human digestive system material for fifth-grade students. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research procedure included needs analysis, media design, product development and validation, student trials, and evaluation and revision. Data were analyzed descriptively quantitatively using a percentage score to determine the level of validity and practicality of the media. The validation results obtained a score of 95% from media experts and 93% from material experts, both categorized as very valid. Practicality obtained a score of 90% in small group trials, 94.2% in field trials, and 93.3% based on teacher responses, all categorized as very practical. Thus, the T'Smart media meets the criteria of being very valid and very practical to be used as a learning medium for class V science on the human digestive system material through interactive game activities.